The novel histologic International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification system of lung adenocarcinoma is a stage-independent predictor of survival - Warth, Arne; Muley, Thomas; Meister, Michael; Stenzinger, Albrecht; Thomas, Michael; Schirmacher, Peter; Schnabel, Philipp Albert; Hoffmann, Hans; Weichert, Wilko (Journal of clinical oncology, 2012)
Purpose Our aim was to analyze and validate the prognostic impact of the novel International Association for the Study of Lung Cancer (IASLC)/American Thoracic Society (ATS)/European Respiratory Society (ERS) proposal for an architectural classification of invasive pulmonary adenocarcinomas (ADCs) across all tumor stages. Patients and Methods The architectural pattern of a large cohort of 500 patients with resected ADCs (stages I to IV) was retrospectively analyzed in 5% increments and classified according to their predominant architecture (lepidic, acinar, solid, papillary, or micropapillary), as proposed by the IASLC/ATS/ERS. Subsequently, histomorphologic data were correlated with clinical data, adjuvant therapy, and patient outcome. Results Overall survival differed significantly between lepidic (78.5 months), acinar (67.3 months), solid (58.1 months), papillary (48.9 months), and micropapillary (44.9 months) predominant ADCs (P = .007). When patterns were lumped into groups, this resulted in even more pronounced differences in survival (pattern group 1, 78.5 months; group 2, 67.3 months; group 3, 57.2 months; P = .001). Comparable differences were observed for overall, disease-specific, and disease-free survival. Pattern and pattern groups were stage- and therapy-independent prognosticators for all three survival parameters. Survival differences according to patterns were influenced by adjuvant chemoradiotherapy; in particular, solid-predominant tumors had an improved prognosis with adjuvant radiotherapy. The predominant pattern was tightly linked to the risk of developing nodal metastases (P < .001). Conclusion Besides all recent molecular progress, architectural grading of pulmonary ADCs according to the novel IASLC/ATS/ERS scheme is a rapid, straightforward, and efficient discriminator for patient prognosis and may support patient stratification for adjuvant chemoradiotherapy. It should be part of an integrated clinical, morphologic, and molecular subtyping to further improve ADC treatment.